Analysis of the influence of attitude toward using, behavioral intention and actual use of the Elsimil application on future brides - Siregar, Sri Astuti; Lanita, Usi; Wardiah, Rizalia; Sitanggang, Hendra Dhermawan (Proceedings Academic Universitas Jambi, 2025)
Background: The Elsimil application is designed as a digital innovation to conduct health screenings for prospective brides and grooms, provide education, and nutritional recommendations three months before the wedding. The main objective is to ensure the couple's readiness to prevent the risk of stunting in children. Based on empirical findings in several regions, the main challenges include limited digital infrastructure, low technological literacy, and a lack of understanding and expertise of users in accessing the application. These problems lead to low levels of compliance and intention to use the application, as indicated in several case studies. This low adoption indicates a gap between sophisticated technological design and actual acceptance by target users. Objective: This study aims to analyze the influence of attitudes towards the use, intention to use, and actual use of the Elsimil application on prospective brides and grooms. Methods: This study uses a quantitative method with a cross-sectional approach with a sample of 100 female prospective brides and grooms in Jambi. The researcher used primary data as initial data collected through questionnaires. Data analysis was carried out using SEM-PLS software. Results: The results of the measurement model test indicate that most indicators have outer loading ≥ 0,7, so that it meets the validity criteria convergent, all latent variables are proven to be reliable with Composite Reliability >0.7 and convergent validity good (AVE >0.5). In addition, the discriminant validity test shows that the square root of the AVE of each variable is greater than the correlation between variables, so that each latent variable has adequate discriminant validity. Conclusion: The results of the hypothesis test indicate that attitude toward using (ATU) positively and significantly influences behavioral intention (BI), behavioral intention (BI) positively and significantly influences actual use of system (AU).